PENGARUH TEKANAN OVERBURDEN TERHADAP POTENSI DAN TEKANAN PENGEMBANGAN TANAH EKSPANSIF - , Alfian Adie Chandra ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Expansive soil problem is the volume change due to the process of shrinkage caused by the change in moisture content. The variation of overburden pressure can result in different values of swelling potential and swelling pressure on the same type of soil. This research is intended to study the swelling behaviour of expansive soil from Sooko-Ngawi, East Java Province by giving various overburden pressures. Swelling test used oedometer with various overburden presurre. The result was expected to study the characteristics of expansive soil (swelling potential and swelling presurre) with various pressures. The results of the test showed, that variation at overburden pressure influenced the swelling and swelling presurre value. Curve relation of strain-overburden presurre with variaous of overburden pressure and 6.9 kPa initial overburden presurre did not coincide because the variation of initial overburden pressure was also influenced by the swelling time.